2008
DOI: 10.4049/jimmunol.181.3.1814
|View full text |Cite
|
Sign up to set email alerts
|

Activated CD8 T Cells Redistribute to Antigen-Free Lymph Nodes and Exhibit Effector and Memory Characteristics

Abstract: Exogenous dendritic cells display restricted trafficking when injected in vivo and stimulate CD8 T cell responses that are localized to a small number of lymphoid compartments. By examining these responses in the presence and absence of FTY720, a drug that causes sequestration of T cells in lymph nodes, we demonstrate that a significant fraction of divided CD8 T cells redistribute into Ag-free lymph nodes within 3 days of activation. Despite variation in the level of expression of CD62L, redistribution of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 54 publications
(91 reference statements)
1
31
0
Order By: Relevance
“…NS: non significant. presence of alum, or intratracheal injection of DC [35,[42][43][44][45][46], but the phenotype and responsiveness of these early emigrants had not been characterized within distant Ag-free nodes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NS: non significant. presence of alum, or intratracheal injection of DC [35,[42][43][44][45][46], but the phenotype and responsiveness of these early emigrants had not been characterized within distant Ag-free nodes.…”
Section: Discussionmentioning
confidence: 99%
“…They have lost the phenotype of naïve cells, for they lack CD45RB while expressing CD44 and CD11a. They express CD62L [35] and in most cases re-express IL-7Ra [47] and are non-proliferating Ki67 cells. These cells also lack the early activation markers CD69 and CD25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central memory T cells migrating through tertiary tissues adopt effector memory phenotype and function, indicating a high degree of plasticity in memory populations that can be shaped by organ-specific influences (14). In support of this notion, recent studies detected significant numbers of CD62L pos effector T cells in draining lymph nodes early after infection that gave rise to memory T cells at high frequencies (15,16). These findings raise the question as to whether T cells that home frequently to lymph nodes during their transition from effector to memory stages will preferentially adopt central memory phenotype and functional attributes.…”
mentioning
confidence: 91%
“…[14][15][16][17] In addition, cessation of stimulation has been proposed as a necessary step for effector to memory cell transition. [18][19][20] TCR signalling intensity has been established as a key parameter for memory T-cell formation. Some studies showed that persistent or strong stimulation through the TCR can dampen memory generation.…”
Section: Introductionmentioning
confidence: 99%